The Effect Of Fluoride Varnish Application On Microhardness And Structural Integrity Of Primary Teeth After Radiation Therapy: An In-Vitro Study (Journal of Pharmaceutical Negative Results, 2023)
Aim: To evaluate the effect of fluoride varnish on microhardness and structure of primary teeth after radiation.Materials and Methods: Total thirty-six specimens of primary teeth were taken in this study, about twenty- four specimens were subjected to radiotherapy and twelve specimens were considered as control group. The specimens were divided into primary molars group (Group 1), irradiated primary molars group (Group 2) and irradiated fluoride varnish primary molars group (Group 3). The specimens from each group were subjected to microhardness, and scanning electron microscopy (SEM) analysis. The calcium and phosphate concentrations of artificial saliva was determined. The data was subjected to inter group comparison, which was done using one way ANOVA followed by pair wise comparison using post hoc test.Results: This study showed that enamel surface hardness of irradiated fluoride varnish primary molars group (367.13± 58.0 kgf/mm2) was higher than that observed on primary molars group (328.4 ± 59.5 kgf/mm2). (p<0.001) The dentin surface hardness was highest in primary molars group (56.05 ± 5.5 kgf/mm2) and least in irradiated primary molars group (25.8 ± 4.2 kgf/mm2) (p<0.001). SEM images showed cracks on enamel and degradation of peritubular dentin in irradiated primary molars group.Conclusion: The application of 5% sodium fluoride varnish during the irradiation treatment preserved the morphological and chemical integrity of the irradiated teeth.